A COMPARATIVE CLINICAL STUDY OF VARUNADI KWATH AND TRIVIKRAM RASA ON MUTRASHMARI W. S. R. TO UROLITHIASIS - Saini Prashant; B.B.Pandey; Ashok Kumar; P.Hemantha Kumar; pareek Ashish (International Journal of Applied Ayurved Research, 2015)
Acharya Sushruta has mentioned Mahagada which literally means grave disease which is difficult to treat and cause tremendous misery to sufferer. Mutrashmari is one among these Mahagada.Symptoms of Ashmari can be correlated with those of urolithiasis described in modern surgical literature. Treatment of urolithiasisis chiefly surgical but at times results are not satisfactory or there is major concern regarding recurrence. Medical treatment as a main treatment or as an adjuvant to overcome recurrence has always been under investigation. In Ayurveda there have been many formulations available for treatment of Ashmari among which Varunadi Kwath and Trivikram Rasa has been indicated in Ashmari. A clinical trial was planned to evaluate the efficacy in patients of urolithiasis. Study was conducted according to special protocol designed for this purpose and the same was approved by competent authorities prior to commencement of study. Thirty nine patients were registered for the clinical trial and 30 patients completed trial and data obtained were used for interpretation and for drawing conclusion. Varunadi Kwath provided significant relief in pain (54.55%), burning micturition (58.33%), dysuria (61.54%), hematuria (87.50%), WBC count of urine (52.63%), size of calculus (52.94%) and no. of calculus (52.94%). Trivikram Rasa provided significant relief in pain (53.85%), burning micturition (43.75%), dysuria (53.85%), hematuria (75.00%), WBC count of urine (45.00%), size of calculus (42.86%) and no. of calculus (50.00%).